Football Hooligans in the Czech Republic: Selected Topics - Smolík, Josef (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2012)
Since the 1990s organized groups have begun to appear in the Czech Republic called „football hooligans”. These groups have drawn the attention of the media, security forces, officials of the Czech Republic Football Association, and the broader public. This text focuses on selected topics associated with the phenomenon of football hooliganism. After a brief history of football hooliganism abroad, especially in England, it will describe the current status of this phenomenon in the Czech Republic. An important part of the text will be devoted to classifying spectators surveyed at football matches into three groups: the broader football audience, fans, and hooligans. Each of these groups will be given a basic description based on previous research carried out at football stadiums. Another goal of the text will be to present the sociological discussion about this phenomenon in the Czech setting, identify the main research avenues, and present some of the sociological studies done in the Czech Republic in recent years. Another important part of the text will be a conceptualization of individual terms, and a brief history of the phenomenon in the Czech Republic, and in the Czechoslovak Republic prior to 1989. Subsequent passages will present the legislative measures and specific laws that have been adopted to address the phenomenon of football hooliganism.
Chuliganie stadionowi w Republice Czeskiej: wybrane wątki
Keywords: subculture; football hooligan; development of the football hooligan subculture; football hooliganism in the Czech Republic